Pengambilan Kebijakan Pengembangan Industri Nuklir Cina oleh Xi Jinping Melalui Analisa Kode Operasional - Br Silalahi, Bertauli Delima; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   Nuclear policy under the Xi Jinping administration has become a contradiction. Under previous administration, the logic behind its use was centered on the need for cheap electricity and low emissions, but under-utilization of existing reactors and the slowing of economic growth have made that no longer sufficient explanation. Add to these factors, the popular opposition of nuclear development following the Fukushima disaster, and a new explanation becomes necessary. An explanation rooted in China’s current, absolute leader, Xi Jinping. Xi Jinping’s personality offers an analytic approach with the capacity to explain this, because of the large role he plays in making policy in China. This research aims to describe the effect of Xi Jinping’s personality on China’s nuclear development. This research was analyzed by Cognitive Approach concept with Operational Code Framework .   Keywords : Xi Jinping Personality, Nuclear Industry, Cognitive Approach, Operational Code